Toward Safe Lithium Metal Anode in Rechargeable Batteries: A Review - Cheng, Xin-Bing; Zhang, Rui; Zhao, Chen-Zi; Zhang, Qiang (Chemical reviews, 2017)
The lithium metal battery is strongly considered to be one of the most promising candidates for high-energy-density energy storage devices in our modern and technology-based society. However, uncontrollable lithium dendrite growth induces poor cycling efficiency and severe safety concerns, dragging lithium metal batteries out of practical applications. This review presents a comprehensive overview of the lithium metal anode and its dendritic lithium growth. First, the working principles and technical challenges of a lithium metal anode are underscored. Specific attention is paid to the mechanistic understandings and quantitative models for solid electrolyte interphase (SEI) formation, lithium dendrite nucleation, and growth. On the basis of previous theoretical understanding and analysis, recently proposed strategies to suppress dendrite growth of lithium metal anode and some other metal anodes are reviewed. A section dedicated to the potential of full-cell lithium metal batteries for practical applications is included. A general conclusion and a perspective on the current limitations and recommended future research directions of lithium metal batteries are presented. The review concludes with an attempt at summarizing the theoretical and experimental achievements in lithium metal anodes and endeavors to realize the practical applications of lithium metal batteries.